A Study of the Effectiveness of the Main Online Advertising Tools Used by Companies in Romania - Lucia Nicoleta BARBU; Ionut TANASE (Communications of International Proceedings, 2023)
In the continuously expanding digital era, online advertising has become one of the essential pillars of companies' marketing strategies worldwide. Romania is no exception, with organizations of all sizes directing their resources to online platforms to promote their products and services. However, for online advertising investments to be effective, it is imperative to truly understand how different advertising tools work and identify the most suitable ones to achieve a company's specific objectives. The purpose of this paper is to highlight the efficiency of the main online advertising tools used by companies in Romania and assess the impact these tools have on users. The methodology applied in this study focused on a questionnaire consisting of questions and was implemented on a sample of 110 respondents. The objective was to determine to what extent online advertising used by companies in Romania influences consumers' purchase decisions. The results obtained from the research revealed that the online advertising tools adopted by companies have a significant impact on the decision-making process for the purchase of products and services. However, it is important to note that this study has certain limitations. One of these aspects is the relatively small number of respondents who participated in the survey.The practical implications of these findings emphasize the need for marketing specialists to develop advertisements that convey strong emotions, relevant and credible content in promoting products and services. The originality of this study lies in the fact that, in the current context, the effectiveness of online advertising is an essential indicator for companies, and this research contributes to a deeper understanding of its effects on consumers. This study provides relevant information regarding the efficiency of the main online advertising tools used by companies in Romania.
Keywords: Efficiency; Online Advertising; Online Advertising Tools; social media; Search Advertising; Display Advertising; Email; Mobile Advertising; Companies